Targeting Cancer Stem Cells for Treatment of Glioblastoma Multiforme. Issue 4 (April 2013) - Cho, Der-Yang; Lin, Shinn-Zong; Yang, Wen-Kuang; Lee, Han-Chung; Hsu, Den-Mei; Lin, Hung-Lin; Chen, Chun-Chung; Liu, Chun-Lin; Lee, Wen-Yuan; Ho, Li-Hui
Cancer stem cells (CSCs) in glioblastoma multiforme (GBM) are radioresistant and chemoresistant, which eventually results in tumor recurrence. Targeting CSCs for treatment is the most crucial issue. There are five methods for targeting the CSCs of GBM. One is to develop a new chemotherapeutic agent specific to CSCs. A second is to use a radiosensitizer to enhance the radiotherapy effect on CSCs. A third is to use immune cells to attack the CSCs. In a fourth method, an agent is used to promote CSCs to differentiate into normal cells. Finally, ongoing gene therapy may be helpful. New therapeutic agents for targeting a signal pathway, such as epidermal growth factor (EGF) and vascular epidermal growth factor (VEGF) or protein kinase inhibitors, have been used for GBM but for CSCs the effects still require further evaluation. Nonsteroidal anti-inflammatory drugs (NSAIDs) such as cyclooxygenase-2 (Cox-2) inhibitors have proven to be effective for increasing radiation sensitivity of CSCs in culture. Autologous dendritic cells (DCs) are one of the promising immunotherapeutic agents in clinical trials and may provide another innovative method for eradication of CSCs. Bone-morphogenetic protein 4 (BMP4) is an agent used to induce CSCs to differentiate into normal glial cells. Research on gene therapy by viral vector is also being carried out in clinical trials. Targeting CSCs by eliminating the GBM tumor may provide an innovative way to reduce tumor recurrence by providing a synergistic effect with conventional treatment. The combination of conventional surgery, chemotherapy, and radiotherapy with stem cell-orientated therapy may provide a new promising treatment for reducing GBM recurrence and improving the survival rate.